2009
DOI: 10.1002/ejoc.200900547
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Conjugate Addition of Acetylacetone to Nitroolefins with Chiral Organocatalysts Derived from Both α‐Amino ­Acids and Carbohydrates

Abstract: Bifunctional chiral tertiary amine thioureas derived from both α-amino acids and carbohydrates were developed. These organocatalysts promoted the enantioselective conjugate addition of acetylacetone to various aromatic and aliphatic nitroolefins at room temperature in good yields (up to 93 %) and with good enantioselectivity (up to 90 % ee). Furthermore, an interesting matched-mismatched effect of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 46 publications
0
10
0
1
Order By: Relevance
“…Interestingly, in our previous enantioselective Michael reactions between 1,3‐dicarbonyl compounds and nitroolefins,5ac two chiral elements of the catalyst 1a ( R A , S , S ) were found to be matched, whereas two chiral elements of the catalyst 1b ( R A , R , R ) were mismatched. The bifunctional thioureas 1c and 1d 5ad, ae developed by us recently provided product 4a in 67 % ee (entry 3) and −68 % ee (entry 4), respectively. Although Takemoto’s catalyst 1e ,5a which was an excellent catalyst in the Michael addition of malonates to nitroolefins, was evaluated, only 69 % ee was obtained in the current reaction (entry 5).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, in our previous enantioselective Michael reactions between 1,3‐dicarbonyl compounds and nitroolefins,5ac two chiral elements of the catalyst 1a ( R A , S , S ) were found to be matched, whereas two chiral elements of the catalyst 1b ( R A , R , R ) were mismatched. The bifunctional thioureas 1c and 1d 5ad, ae developed by us recently provided product 4a in 67 % ee (entry 3) and −68 % ee (entry 4), respectively. Although Takemoto’s catalyst 1e ,5a which was an excellent catalyst in the Michael addition of malonates to nitroolefins, was evaluated, only 69 % ee was obtained in the current reaction (entry 5).…”
Section: Resultsmentioning
confidence: 99%
“…Of the different H‐bond donor catalysts reported to date, those based on the thiourea core dominate the field. Thus, new thioureas or other hydrogen bond donors from accessible members of the chiral pool are continuously being developed . Over the past few years, bifunctional tertiary amine‐thiourea organocatalysts have emerged as new and efficient organocatalysts for asymmetric reactions .…”
Section: Methodsmentioning
confidence: 99%
“…Thus, new thioureas or other hydrogen bond donors from accessible members of the chiral pool are continuously being developed. [19][20][21][22][23][24][25][26][27][28][29] Over the past few years, bifunctional tertiary amine-thiourea organocatalysts have emerged as new and efficient organocatalysts for asymmetric reactions. 30,31 It was found that the cinchona alkaloid family and its derivatives as the chiral amine parts of catalysts possessed high catalytic activity resulting in a high ee value in the asymmetric Michael addition.…”
mentioning
confidence: 99%
“…Bifunctional chiral organocatalysts derived from α‐amino acids and carbohydrates and each containing a thiourea function were developed by Shao and co‐workers in 2009 27. These catalysts were found to promote Michael addition of acetylacetone to aromatic nitro olefins and to 4‐methyl‐1‐nitropent‐1‐ene in good yields and with good enantioselectivities (Scheme ).…”
Section: Carbohydrate‐based Amine–(thio)ureasmentioning
confidence: 99%